Peer review of the pesticide risk assessment of the active substance etoxazole. (9th October 2017) - ,; Arena, Maria; Auteri, Domenica; Barmaz, Stefania; Bellisai, Giulia; Brancato, Alba; Brocca, Daniela; Bura, Laszlo; Byers, Harry; Chiusolo, Arianna; Court Marques, Daniele; Crivellente, Federica; et al.
Abstract: The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Greece, and the co‐rapporteur Member State, the United Kingdom, for the pesticide active substance etoxazole and the assessment of applications for maximum residue levels (MRLs) are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of etoxazole as an acaricide on pome fruits, plums, peaches, nectarines, apricots, cherries (sweet), citrus, grapes, strawberries, tomatoes/eggplants, cucurbits inedible peel, cotton seeds and ornamental plants. MRLs were assessed in strawberries, cucurbits inedible peel, plums, tomatoes and aubergines/eggplants. The reliable end points, appropriate for use in regulatory risk assessment and the proposed MRLs, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.